(untitled) (Research, Society and Development, 2020)
The Brazilian agri-food business has undergone reforms in its regulatory frameworks, which aim at promoting and making food production more competitive. Among the new regulatory frameworks is the Decree 9,918/2019, known as the Art Seal law, which establishes the criteria and supervision of the production of artisanal food of animal origin. The present study aimed to understand which competitive advantages the Law can promote to artisanal agri-food businesses of animal origin, through the theoretical articulation of the competitiveness models proposed by Porter (1993), Esser, Hillebrand, Messner & Meyer-Stamer (1996) and Farina (1999). Documentary and bibliographic consultations made it possible to understand that the ability to generate competitive advantages, especially for producers who are in the informal sector, is closely linked to the competence of the Public Power and related institutions to establish technical parameters that preserve food safety without imposing new costs to productive activities. In this sense, considering that assumptions of the Decree 9,918 / 2019 consists of simplifying the process of registration and regulation of products originating from small rural properties, enabling its commercialization in national scope, and adding value to them, keeping their particularities, it was verified that Decree 9,918 / 2019 does not bring institutional innovation that can promote greater competitiveness to businesses linked to the production of artisanal foods of animal origin.